Colonization profile and microbiological resistance in Intensive Care Unit (ICU) patients in the city of Anápolis – GO (Research, Society and Development, 2021)
One of the biggest global health concerns today is the microbial resistance to antibiotics, which contribute to the increase in the mortality rate, the stay in a health institution and favor the colonization process. Thus, colonization is conceptualized as the presence of microorganisms in the human microbiota (intestine, mouth, nose and skin) that do not cause disease or symptoms and can trigger the most varied resistance mechanisms, whether intrinsic or extrinsic. Some of these microorganisms are indispensable for the proper functioning of the human body, however the imbalance of this microbiota can result in complications such as infections. The purpose of this study was to understand the microbiological profile of multidrug-resistant microorganisms in the colonization of patients admitted to Intensive Care Units (ICU) in a private medium-sized and tertiary-level private hospital in the city of Anápolis (GO) from 2017 to 2019, identifying how and when colonizations by such microorganisms occurred. This study was a documentary, retrospective, descriptive and cross-sectional research and the data collection was carried out after appreciation and favorable opinion from the Research Ethics Committee of UniEVANGÉLICA via Plataforma Brasil. As a result, a colonization rate of 6% of the studied sample was observed, 67% of which had Klebsiella sp. Several factors were identified that contribute to the development of colonization and bacterial resistance, including the prevalence of the elderly (74.28%), use of invasive devices (100%), antibiotic use longer than 7 days (42.4 %) and length of stay greater than 48 hours (95.17%). It was concluded, then, that the patients in the present study were submitted to risk conditions, as portrayed in the studied literature, for colonization and bacterial resistance. In addition, the most prevalent bacteria in the ICU studied was Klebsiella sp, as expected according to the studies carried out.